Improvement of clinical parameters in HDV patients with advanced compensated cirrhosis treated with Bulevirtide monotherapy for 48 weeks. (March 2023) - Degasperi, E.; Anolli, M.P.; Renteria, S.C. Uceda; Sambarino, D.; Borghi, M.; Perbellini, R.; Facchetti, F.; Loglio, A.; Monico, Sara; Fraquelli, M.; Costantino, A.; Ceriotti, F.; et al.
Abstract : Background and Aim: Bulevirtide (BLV) has been conditionally approved for treatment of compensated chronic hepatitis Delta in Europe, however long-term outcomes of HDV patients with compensated cirrhosis treated with BLV monotherapy are currently unknown. Methods: Consecutive HDV patients with compensated cirrhosis who received BLV monotherapy for 48 weeks were enrolled in this single-center study. Clinical variables were collected at baseline, weeks 4, 8 and every 8 weeks thereafter. Results: 20 Caucasian patients under nucleos(t)ide analogue (NUC) treatment were included: median age 49 years, 65% males, liver stiffness measurement (LSM) 16.8 kPa, 80% with varices. At baseline, ALT levels were 110 U/L, AST 92 U/L, GGT 52 U/L, albumin 3.9 g/dL, platelets 72 × 10 3 /mm 3, IgG 2285 mg/dL, HDV RNA 4.9 UI/mL. CPT score was A in all patients. Following 48 weeks of BLV monotherapy (2 mg/day in n=18 and 10 mg/day in n=2), HDV RNA declined by 3.1 Log IU/mL and became undetectable in 39%; 89% of patients achieved a virological response (undetectable HDV RNA or ≥2 Log decline vs. baseline). At week 48, most biochemical parameters improved: ALT (normalizing in 85% of patients), AST, GGT, IgG and albumin (p<0.001 for all comparisons). Four out of 5 patients with CPT score A6 improved to A5 at week 48. Bilirubin, platelets and HBsAg remained unchanged, LSM significantly declined in viral responder patients (p=0.03). Among 9 patients with baseline small varices not needing prophylaxis, varices disappeared in 2 cases. De-novo decompensation due to portal vein thrombosis occurred in one patient, de-novo HCC in two, three underwent liver transplantation and one patient died due to BLV-unrelated causes. BLV was well tolerated, an asymptomatic increase in bile acids occurred. Conclusions: Liver function parameters improved in HDV patients with compensated cirrhosis treated with BLV monotherapy for 48 weeks. Esophageal varices disappeared in some patients.